Alternative farming on the highland and livelihood assets of small scale farmers in Na Noi District, Nan Province, Thailand - Priyanud Chuensin; Budsara Limnirankul; Prathantip Kramol (Songklanakarin Journal of Science and Technology (SJST), 2022)
The livelihood assets of small-scale farmers described problems and situations of alternative farms on the highland of Na Noi district. The research methods involved key informant’s interviews, focus group discussions, and questionnaires with 222 samples who have alternative farming on the highland of Na Noi district. Data analysis used a sustainable livelihood assets framework, which included both quantitative and qualitative analysis. According to data collection, alternative farming systems were: 56 households of maize and rubber tree farming, 153 households of maize, rubber tree, and integrated farming, and 13 households of integrated farming. Analysis between farm types and their livelihood assets found that farmers have different accessibility of natural assets, human assets, social assets, financial assets, and physical assets. It was the ability to reduce their vulnerabilities. Alternative farm types have contributed by the accessibility of their livelihood assets. Thus, to promote the alternative farming systems should consider their livelihood assets.